Living In a Boarding House: A Privacy Mechanism in Architecture Student’s Private Study Room - Purwanita Setijanti; Sarah Cahyadini; Tisya Surya Narida (Journal of Architecture & Environment, 2023)
Boarding house as a type of temporary residence functions to ensure the continuity of daily domestic activities, as well as a comfortable place to study for students as its occupants. The multimodal method employed in architectural studio learning requires using more than one strategy in the learning process, such as through design simulations or making study models. As a result, compared to the unimodal approach, there are spatial consequences for learning privacy that affect individual and group learning processes. This research explores the privacy mechanism in boarding rooms as private workspaces for architecture students. Phenomenological qualitative methods are applied, with data collection techniques ranging from observation, interviews, and sketches to document readings. The research findings show that architecture students optimize space by modifying spatial attributes such as layout, wall openings, material and furniture. This ensures that learning takes place in the maximum privacy possible, enabling a practical function of multimodal learning activities.